DAMPAK PEMBELAJARAN BERBASIS MASALAH (PBL) TERHADAP PENGEMBANGAN KETERAMPILAN PEMECAHAN MASALAH SISWA PADA MATA PELAJARAN MATEMATIKA - Muhammad Furqan (PENCERAHAN, 2023)
The objective of this study is to look into the effectiveness of instructional videos using the Problem-Based Learning Method in developing problem-solving skills in primary school students. To improve students' problem-solving skills, this study incorporated instructional material related to math topics " mixed count operation " into video. The experimental research method was used to achieve the study's goal. The model was implemented in three primary public schools in Aceh Utara, Indonesia, with 260 grade 6 students participating. A pretest and posttest were given before and after the treatment. The findings show that there was a statistically significant difference between the pretest and posttest scores at the significant level.